Physiochemical Analysis of Sewage Sludge in Taj Baj Khan Pokhara, Hajipur, Vaishali, Bihar - Jyoti, Gyan; Kumar, Vijay (American Journal of Biology and Natural Sciences, 2025)
Physiochemical analysis of Taj Baj Khan Pokhara, situated South of Subhash Chowk, Hajipur, Vaishali, Bihar, India. Carried out from January 2024 to December 2024, during the analysis the limnological factors such as color, odor, temperature, acidity, electrical Conductivity, pH, sulphate, chloride, total hardness, total dissolved solid, DO, BOD, COD and alkalinity were taken into consideration and the data were recorded and analyzed. In this study, the air temperature range is from 18°c to 33°c, whereas water temperature ranges from 17°c to 32.8°c. pH ranges from 8.4 in August to September. The lowest value of DO was observed in May (4.2 mg/l) and the highest value was observed in November (13.2 mg/l). Free carbon dioxide varies from 2.5 mg/l to 10.4 mg/l. Chloride content ranges from 71 mg/l to 164.4 mg/l. Alkalinity level ranges from 82 mg/l to 164.4 mg/l, whereas phosphate level was in between 0.42 mg/l and 0.84 mg/l. According to the above result, the selected pond is suitable for fish culture, but continuous monitoring of all the parameters is necessary.